A compreensão de texto argumentativo por adultos idosos e sua relação com componentes cognitivos e escolaridade - Elias, Vanessa Santos (2011)
The collection of life experiences of an individual is increasingly associated with the decrease in the risk of developing dementias and with the reduced rhythm of cognitive functions decline in normal aging (STERN, 2009). Researchers highlight the fact that the relation with cognitive decline is inversely proportional to the level of education. Parente et al. (2008), La Rue (2010), Tucker and Stern (2011) posit that a higher level of formal education does not modify the course of chronic diseases. However, it allows for the possibility of interventions which aim at postponing the emergence and progression of symptoms. Data from INAF (2009) indicate that it is not always the case that schooling guarantees the level of abilities desired. Besides having gone to school, the individual should have good reading habits and should be able to attribute meaning to what is read. The objective of this study was to analyze the comprehension of a narrative text by older and young adults of different schooling levels and to correlate their performances in episodic and working memory evaluation tasks and executive functions. The subjects were 48 individuals of both genders divided into two age groups. The first group composed by 24 young adults, ages between 20 and 35; and the second formed by 24 elder adults, ages between 60 and 75. The Scale of Geriatric Depression reduced (ALMEIDA; ALMEIDA, 1999) and the Mini Mental State Examination (CHAVES, 2011) were used as instruments for including participants in the study. They were submitted to a neuropsychological evaluation composed by the Rey Auditory Verbal Learning Test (REY, 1964), an auditory span of words in a sentence subtest taken from Instrumento de Avaliação Neuropsicológica Breve NEUPSILIN (FONSECA et al., 2009) and the Free Lexical Evocation with orthographic and semantic criteria from the Montreal Communication Evaluation Battery MAC battery (FONSECA et al., 2009An argumentative text, followed by questions presented with the software E-prime, was used in order to evaluate reading comprehension. Performance comparison between the age groups was made with Two-Way ANOVA, having age and schooling effects controlled. Moreover, Pearson correlation analysis was performed to verify the relation among the dependent variables. p≤0,05 was considered for both analyses. Results indicate that schooling effect was more prominent than age for text comprehension tasks. Age and schooling demonstrated effects on variables related to episodic and semantic verbal memory as well as working memory. Nevertheless, only the schooling variable showed effect on executive functions tasks. This study evidenced that, throughout the aging process, schooling is more likely to determine brain function and to characterize behavior of different age groups than age itself.